Traumatic Orbital Compression Syndromes: A Comprehensive Study Into Etiologies, Intervention Strategies, and Clinical Outcomes - Dos Santos, José Cleveilton [UNESP]; de Oliveira Gorla, Luis Fernando [UNESP]; Moreno, Roberto; Monnazzi, Marcelo Silva [UNESP]; Filho, Valfrido Antonio Pereira [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP] (Wolters Kluwer, 2024)
Facial fractures and their historical link to potential blindness have been well-documented, often attributed to optic canal injuries or retinal vascular occlusion. This dire consequence can result from both direct and indirect ocular trauma, including retrobulbar hemorrhage. Traumatic orbital compression can manifest in various forms, such as hematomas, fractured bone fragments, and emphysema, all posing a significant threat to vision, necessitating immediate intervention. In this study, 9 clinical cases of traumatic orbital compression are presented, each characterized by distinct etiologies. The study delves into traumatic orbital compressive syndromes, underscoring the critical imperative of early recognition and treatment to prevent vision loss. Orbital compression, whether from edema, hematoma, or emphysema, collectively culminates in elevated intraorbital pressure and the potential for optic nerve ischemia. Through the presentation of these 9 clinical cases, the article emphasizes the pressing need for timely intervention in addressing orbital compressive syndromes to avert vision loss. Various surgical techniques are elucidated, highlighting the pivotal role of expeditious medical intervention. This article offers invaluable insights into the diagnosis, management, and outcomes of traumatic orbital compressive syndromes.
Keywords: Optic nerve injuries; orbital fracture; retrobulbar hemorrhage